"Talking about race is exhausting": social work educators' experiences teaching about race and racism. Issue 3 (3rd September 2022) - Perez, Ebony Nicole
ABSTRACT: Understanding the impact of race on the enduring racial disparities and inequities throughout our institutions is a key tenet of social work competency. The purpose of this qualitative case study was to investigate the experiences of undergraduate social work educators (BSWEs) who teach the required diversity course. Participants reported the primary challenges teaching about race and racism were: (1) faculty racial identity and lack of credibility (2) emotional toll of teaching about race. This study has implications concerning educators' preparation to engage in anti-racist and equitable pedagogy in undergraduate social work education programs.